Trade implies law the power of the weak - Anderson, James E. 1943-; Young, Leslie (NBER working paper series, 2000)
Without the rule of law, traders who incur trading costs can be held up by counter-parties who are stronger in anarchic bargaining. The favourable terms which the latter extract can overcrowd that side of the market, dissipating the benefits. We establish plausible necessary and sufficient conditions for a move from anarchy toward the rule of law to benefit all traders. The rule of law might be delayed, not only by the difficulties of setting up legal institutions, but by monopolistic traders that have meantime emerged to address the inefficiencies of anarchic trade. These monopolistic traders must also guarantee atomistic traders against holdup.